Computing Versus Human Thinking. - Naur, Peter (Communications of the ACM, 2007)
The article discusses computing versus human thinking. In the article, the author works to develop a new form of description that continues the work of John Backus. The article discusses human knowing as it applies to computer programming. The author concludes that computing presents a form of description, and that this form useful in describing many things about the world, but it is not valuable in describing human thinking. The article discusses the works of William James and Alan Turing.